Global Protests and Cosmopolitan Publicity: Challenging the Representative Claims of Nation-States. Issue 5 (29th July 2017) - Bray, Daniel
Abstract: In the past decade, a global wave of protests has spread to both liberal democratic and authoritarian countries in which the representative claims of nation-states have been profoundly challenged. This article explores the extent to which these protest movements reflect cosmopolitan practices and possibilities. The central argument is that the protests created forms of 'cosmopolitan publicity' in which people engaged in transnationally connected social criticism and political contestation directed at rupturing the representative authority of their state. The article first provides an account of cosmopolitan publicity, arguing that it is produced by interaction across territorial and cultural borders in which open and egalitarian publics are formed to deal with shared problems. It then argues that varying degrees of cosmopolitan publicity were generated in the recent global protests by examining the transnational communication, tactics, and claims of the Arab Spring and Occupy social movements. Finally, the article argues that these protests are indicative of ongoing crises of representation that plague many nation-states and create opportunities for new forms of cosmopolitan politics.